2010
DOI: 10.1016/j.apcata.2010.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and performance of noble metal phosphides supported on silica as new hydrodesulfurization catalysts

Abstract: Preparat ion o f no ble met al (NM) (Rh, Pd, Ru, Pt) phosphide species and t heir cat alyt ic act ivit ies for hydrodesulfur izat ion (HDS) of t hiophene w er e invest igat ed. Noble met al phosphides (NM X P Y) cat alyst s were prepared by reduct ion o f Padded NM (NM-P) support ed on silica (S iO 2) wit h hydrogen. Hydrogen co nsumpt io n peaks at around 350−700 °C, which wer e at t ribut ed t o t he for mat io n o f NM X P Y , were obser ved in t emper at ure-programmed reduct io n (TPR) spect ra of al l NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 29 publications
(13 reference statements)
1
63
0
Order By: Relevance
“…Below 150°C, the spectra for the PdP and RhP catalysts contained peaks (the decomposition of Pd hydride and reduction of Rh 2 O 3 ) similar to those in the spectra of the Pd and Rh catalysts, 10 assuming that the peaks observed above 150°C are attributed to the reduction of phosphate. In the spectrum of the PdP(acac) catalyst, H 2 consumption peaks were observed at 295 and 775°C.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Below 150°C, the spectra for the PdP and RhP catalysts contained peaks (the decomposition of Pd hydride and reduction of Rh 2 O 3 ) similar to those in the spectra of the Pd and Rh catalysts, 10 assuming that the peaks observed above 150°C are attributed to the reduction of phosphate. In the spectrum of the PdP(acac) catalyst, H 2 consumption peaks were observed at 295 and 775°C.…”
mentioning
confidence: 94%
“…2,1014 We reported that Rh 2 P and Pd 4.8 P showed higher catalytic activity than Ni 2 P and other NM X P Y (Ru and Pt). 10 On the other hand, supported Pt catalysts prepared from acetylacetonato (acac) complexes have higher HDS activity than supported Pt catalysts prepared from other precursors. 15 Thus, it may be possible to prepare highly active NM X P Y catalysts from acac complexes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, nickel phosphide (Ni2P) catalyst, which has high HDS activity, has been widely studied 1) 6) . We previously reported noble metal phosphides supported on SiO2 as a new type of HDS catalyst 7) . The rhodium phosphide (Rh2P) catalyst showed the highest activity among various noble metal phosphides, with equivalent activity to the commercial Co _ Mo catalyst 7) .…”
Section: Introductionmentioning
confidence: 99%